Global premature mortality by dust and pollution PM2.5 estimated from aerosol reanalysis of the modern-era retrospective analysis for research and applications, version 2 - Yang, Alexander; Tan, Qian; Rajapakshe, Chamara; Chin, Mian; Yu, Hongbin (Frontiers in Environmental Science, 2022)
This study quantifies global premature deaths attributable to long-term exposure of ambient PM2.5, or PM2.5-attributable mortality, by dust and pollution sources. We used NASA’s MERRA-2 aerosol reanalysis product for PM2.5 and the cause-specific relative risk from the integrated exposure-response model to estimate global PM2.5-attributable mortality for five causes of deaths, namely ischaemic heart disease (IHD), cerebrovascular disease (CEV) or stroke, lung cancer (LC), chronic obstructive pulmonary disease (COPD), and acute lower respiratory infection (ALRI). The estimated yearly global PM2.5-attributable mortality in 2019 amounts to 2.89 (1.38 ~ 4.48) millions, which is composed of 1.19 (0.73 ~ 1.84) million from IHD, 1.01 (0.35 ~ 1.55) million from CEV, 0.29 (0.11 ~ 0.48) million from COPD, 0.23 (0.14 ~ 0.33) million from ALRI, and 0.17 (0.04 ~ 0.28) million from LC (the numbers in parentheses represent the estimated mortality range due corresponding to RR spread at the 95% confidence interval). The mortality counts vary with geopolitical regions substantially, with the highest number of deaths occurring in Asia. China and India account for 40% and 23% of the global PM2.5-attributable deaths, respectively. In terms of sources of PM2.5, about 22% of the global all-cause PM2.5-attributable deaths are caused by desert dust. The largest dust attribution is 37% for ALRI. The relative contributions of dust and pollution sources vary with the causes of deaths and geographical regions. Enforcing air pollution regulations to transfer areas from PM2.5 nonattainment to PM2.5 attainment can have great health benefits. Being attainable with the U.S. air quality standard (AQS) of 15 𝝁g/m3 globally would have avoided nearly 40% or 1.2 million premature deaths. The most recent update of PM2.5 guideline from 10 to 5 𝝁g/m3 by the World Health Organization (WHO) would potentially save additional one million lives. Our study highlights the importance of distinguishing aerodynamic size from geometric size in accurately assessing the global health burden of PM2.5 and in particular dust. A use of geometric size in diagnosing dust PM2.5 from the model simulation overestimates the PM2.5 level in the dust belt by 40-170%, leading to an overestimate of global all-cause mortality by 1 million or 32%.